The Role of Information Technologies in the Management and Sustainability of Land Use in Future Cities (Journal of Planner and Development, 2022)
The most important contemporary issues which related to the survey of the influence of communication development technology to land use sustainability. The research aims to explain the changes that happened in the quality & land use activities performance by understanding the transformations due to modern technology and its impact on current uses and its impact on changing functional relationships between those uses to create new combinations or hybrid uses.Research will follow the analytical descriptive approach in presenting the problem of research. Research has several conclusions & recommendations, one of conclusions is the change of the place concept and its relation to changing the concept of land use and its sustainability, The new foundations for classifying activities and land uses were influenced by the information and communication technologies use, which affected on changing inter-relations of activities and their impact on the changing types and classification of land uses.